Potassium carbonate based deep eutectic solvent (DES) as a potential drilling fluid additive in deep water drilling applications - Rasool, M.H. (Taylor and Francis Ltd., 2021)
Drilling fluid design is the most vital step in drilling phase. An ideal drilling fluid apart from exhibiting good thixotropic behavior should be efficient in inhibiting the hydrates formation, suppressing shale swelling and improving mud rheology. Lately, Ionic Liquids are being used as drilling fluid additives to increase the efficiency of drilling mud. Recent research has given evidences that imidazolium based Ionic liquids are toxic, not biodegradable and their preparation require sophisticated techniques and equipment. Deep Eutectic Solvents (DES) are regarded as fourth generation ionic liquids and are claimed to be the greener and cheaper alternative of traditional ionic liquids. This research utilizes potassium carbonate based DES to check its candidacy as a potential drilling fluid additive. DES based drilling mud showed optimum performance at 0.5 conc. (of DES) by delaying induction time of hydrates formation by 33.8 and decreasing mud cake thickness and filtrate volume by 36 and 24 respectively. Moreover, from a âfree styleâ experiment DES proved to be an excellent shale inhibitor by inhibiting shale swelling upto 84.The inhibiting traits of DES are mainly attributed to its hydrogen bond formation capability with hydrates and clay. Â© 2021 Taylor & Francis Group, LLC.